Analysis of Creative and Productive Learning Strategies in PJOK Subjects - Pratama, Andra; Hartati, Hartati; Aryanti, Silvi (Journal Coaching Education Sports, 2023)
This research aims to analyze the performance of creative and productive learning strategies in the subject of Physical Education and Health (PJOK) for 10th-grade students at SMAN 5 Sekayu. The population of this study consists of 10th-grade students at SMAN 5 Sekayu. The qualitative descriptive method was employed, and the sampling technique used in this study was total sampling, where the entire population was included as the sample, resulting in 35 respondents. Data collection techniques included questionnaires, interviews, and documentation. Data analysis techniques involved data reduction, data presentation, and drawing conclusions. Based on the research findings, it can be concluded that the creative and productive learning strategies in the PJOK subject for 10th-grade students at SMAN 5 Sekayu are categorized as highly effective, accounting for 82.4%. The conclusion of this study is that the analysis of creative and productive learning strategies in the PJOK subject for 10th-grade students at SMAN 5 Sekayu falls under the category of excellent. The implication is that these strategies can be adopted and implemented in other subjects at the same school or similar institutions.